The impact of dietary fibres on the physiological processes of the large intestine. (October 2018) - Gill, Saloni; Chater, Peter I.; Wilcox, Matthew D.; Pearson, Jeffrey P.; Brownlee, Iain A.
Abstract: No endogenous secretion of digestive enzymes occurs within the human large intestine, yet this region of the gut still has an important role in the absorption of water and a range of nutrients. In parallel, the large intestine must also cope with a high load of micro-organisms and an increasing concentration of potentially toxic agents. The duality of these roles (facilitating absorption while effectively partitioning damaging luminal agents) is vital to the proper functioning of the large intestine. The effectors of these roles are the smooth muscle that drives a complex motility and the epithelial lining. The epithelium is arranged in crypts that contain a variety of different cell types whose roles help effect absorption, protection and self-maintenance of the large intestinal epithelium. Digesta remains within the large intestine for much longer than other gastrointestinal compartments and so the composition of the luminal contents may have a greater potential to positively or negatively impact on gastrointestinal and systemic health. The current review aims to consider recent evidence that dietary fibres may impact on the physiological processes of the large intestine, with particular reference to the interplay of fibres with the resident microbiota. Graphical abstract: